Displasia septo-óptica: um relato de caso sobre síndrome de Morsier - Marina Bonagurio Julio; Brenna Marques Amorim Tenorio; Helen Vinco Secchin; Juliana Brizzante Ferreira; Marina Dall'Ara de Souza (Residência Pediátrica)
INTRODUCTION: Septo-optic dysplasia, also known as Morsier Syndrome, is considered a rare congenital disease, with an estimated incidence of 1 in every 100,000 live births and is characterized by the triad: midline defects (corpus callosum agenesis and/or septum pellucidum), optic nerve hypoplasia and hormonal abnormalities of the hypophysis. The clinical changes of the disease are varied, which makes the diagnosis a challenging, but essential to reduce the high morbidity associated with the disease. OBJECTIVE: Report a case of septo-optic dysplasia syndrome and how it came to be diagnosis. CASE REPORT: Male patient, born in a maternity hospital in city of São Paulo, with changes in the initial physical examination: micropenis, macrocrania and nystagmus. The neonatology team questioned the presence of any syndrome. As part investigation of malformations, requested an ophthalmological evaluation that identified bilateral optic nerve hypoplasia. Other findings were hormonal abnormalities of the pituitary glands and, therefore, two of the diagnostic criteria for Morsier Syndrome. CONCLUSION: The pediatrician must be capable of clinical diagnostic reasoning of rare syndromes, as he is the first professional who has contact with the patient, in order to initiate early intervention, reducing associated morbidities.